2013
DOI: 10.1134/s0003683813090044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxic effects evoked by the transient expression of protease genes from human pathogens in HEK293 cells

Abstract: A method for the in vitro evaluation of the toxic effects occurring in human cell lines upon the expression of genes from a range of pathogens is proposed. The method is based on the transient expression of the genes in the HEK293 cell line. Induction of cell death upon the expression of the gene coding for pro tease 3C from the human hepatitis A virus has been demonstrated for the first time using the method pro posed. Expression of the gene coding for protease 2A from human poliovirus has also been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Thus, 3Cpro and its inactive variant 3Cmut were expressed in several model cell lines. Fully compliant with the previous data [ 10 , 11 ], here, we showed that the observed cytotoxic effect of 3Cpro expression depends on the protease activity, and cell death is accompanied by cytoplasmic vacuolization without caspase activation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, 3Cpro and its inactive variant 3Cmut were expressed in several model cell lines. Fully compliant with the previous data [ 10 , 11 ], here, we showed that the observed cytotoxic effect of 3Cpro expression depends on the protease activity, and cell death is accompanied by cytoplasmic vacuolization without caspase activation.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the effect of 3Cpro on human cells in the pCI-based expression system in vitro is similar to that previously reported by us [10,11].…”
Section: Cpro Expression Induces Caspase-independent Cell Death With Cytoplasmic Vacuolizationsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, we demonstrated that hepatitis A virus 3C protease (3Cpro) induces cell death, which is also independent of caspase activity and features a unique cell morphology, specifically, the accumulation of cytoplasmic vacuoles with previously undocumented features. This suggested that the 3Cpro-induced cell death proceeds by an unknown pathway or is a new variant of a known RCD type [10-12].…”
Section: Introductionmentioning
confidence: 99%